Implementation Of Kansei Engineering In System Appearance Design E-Learning (Case Study: Galuh Ciamis University) - Bayu Pamungkas (RISTEC : Research in Information Systems and Technology, 2024)
: E-Leaning is a primary need for carrying out teaching and learning activities, especially at universities. Galuh Ciamis University has an E-Learning called